2020
DOI: 10.2147/cmar.s245941
|View full text |Cite
|
Sign up to set email alerts
|

<p>circ-NRIP1 Promotes Glycolysis and Tumor Progression by Regulating miR-186-5p/MYH9 Axis in Gastric Cancer</p>

Abstract: Background: Gastric cancer (GC) is a severe threat to human life, with high incidence and mortality. Circular RNAs (circRNAs) play crucial roles in the progression of GC. This study attempted to investigate the potential role of circ-NRIP1 and associated action mechanisms in GC cells. Methods: The expression of circ-NRIP1 and miR-186-5p was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability, apoptosis, and migration were assessed by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
(34 reference statements)
0
23
1
Order By: Relevance
“…Under hypoxia, GC cell proliferation, invasion, and EMT by a low expression of HCP5 could be counteracted after the interference of miR-186-5p expression. Liu et al (2020) similarly found that miR-186-5p expression was downregulated in GC tissues and that miR-186-5p knockdown reversed the biofunctional effects and glycolytic activation following circ-NRIP1 silencing in GC cells.…”
Section: Discussionmentioning
confidence: 81%
“…Under hypoxia, GC cell proliferation, invasion, and EMT by a low expression of HCP5 could be counteracted after the interference of miR-186-5p expression. Liu et al (2020) similarly found that miR-186-5p expression was downregulated in GC tissues and that miR-186-5p knockdown reversed the biofunctional effects and glycolytic activation following circ-NRIP1 silencing in GC cells.…”
Section: Discussionmentioning
confidence: 81%
“…The same study also revealed that miR-122 targeted PKM2, which affected the metabolism of HCC. Numerous previous studies have reported the role of miR-186 in mediating glycolysis in several types of cancer; for example, miR-186 inhibited aerobic glycolysis in osteosarcoma cells by decreasing hypoxia-inducible factor 1 expression levels (27); circ-nuclear receptor interacting protein 1 promoted glycolysis and gastric cancer progression by downregulating miR-186-5p expression levels (28); and FOXK1 and/or FOXK2 were discovered to regulate aerobic glycolysis (29). In the present study, bioinformatics analysis predicted that circ-PRKCI targeted miR-186-5p and in turn, miR-186-5p targeted FOXK1.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of this gene has been observed in different human pathological conditions, such as in cancer patients and in preeclamptic pregnancies [ 48 , 49 ]. circNRIP1 has been found differentially expressed in several types of tumor tissues, such as gastric cancer, cervical cancer, and ovarian cancer [ 50 , 51 , 52 , 53 ]. circNRIP1 regulates pathways involved in cell proliferation, migration, and invasion [ 50 , 52 , 53 , 54 ] and may also be involved in chemoresistance mechanisms, representing a possible target for cancer resistance treatments [ 51 , 55 ].…”
Section: Discussionmentioning
confidence: 99%